Synthesis and Structural Study of a New β-Turn Inducer Peptidomimetic Incorporating 1-Amino-1-Aminomethylcyclohexane - María Campos; Victor M. Sánchez-Pedregal; Pablo López-Carracedo; Ramón J. Estévez; Juan C. Estévez (Chemistry Proceedings, 2021)
A new β-turn inducer peptidomimetic incorporating 1-amino-1-aminomethylcyclohexane (compound 3) was synthetized and structurally studied. It was established that there is a rapid conformational equilibrium between the expected β-turn inducer structure and other extended conformations.